Dynamic response of an embedded block impacted by aerated high-velocity jets. Issue 4 (3rd July 2016) - Duarte, Rafael; Pinheiro, António; Schleiss, Anton J.
ABSTRACT: Uplift of blocks from the rock mass at the bottom of plunge pools is the main process of the scouring phenomenon caused by high-velocity jet impact. Although the influence of water and rock on dynamic block ejection has been investigated, no systematic research has been done regarding the influence of air entrainment. This study presents theoretical developments and experimental investigations of the vertical displacements of a block embedded in the pool bottom impacted by aerated plunging jets. The theoretical model reproduces well the measured block vibrations, especially for high-velocity jets where the properties of the air–water mixture inside the fissures are steadier. Block displacements reduce with jet aeration for shallow pools, but, inversely, they increase with jet aeration for deep pools. This confirms that jet aeration reduces jet momentum due to a lower apparent density, but may also increase bottom pressures due to lower velocity decay along the pool depth.